Flow Cytometric DNA Index and Karyotype in Childhood Lymphoblastic Leukemia - Erik Forestier; Gösta Holmgren; Göran Roos (Analytical Cellular Pathology)
Flow cytometric DNA-index (DIFCM) and karyotype were analysed in 82 consecutive children with acute lymphoblastic leukemia (ALL) during a 10 year period. A statistically significant correlation existed between modal chromosome number and DIFCM (p = 0.009). DIFCM could reliably identify leukemias with >51 chromosomes, whereas only three out of 12 cases with modal chromosome numbers between 47–51 were classified as aneuploid by DIFCM. In the pseudodiploid group only one out of 20 leukemias had a DIFCM>1.0. Five leukemias with a diploid karyotype showed an aneuploid DIFCM and in three patients the flow cytometric measurement revealed biclonality undetected by karyotyping. During treatment aneuploid clones could be detected by DIFCM in a substantial number of cases where the cytogenetic analysis was normal, and the opposite was also demonstrated in one case. DIFCM gave prognostic information, showing that cases with a DI >1.12 (corresponding to 51 chromosomes) had a superior outcome with treatment protocols today in use.